Computational investigation of hydrogen storage on scandium–acetylene system. (5th January 2015) - Ma, Li-Juan; Jia, Jianfeng; Wu, Hai-Shun
Abstract: The hydrogen storage capacities of synthesized Scandium–Acetylene systems (Sc– η 2 –(C2 H2 ) and HCC–ScH) are tested by using density functional theory (DFT) and the coupled-cluster theory (CCSD (T)) with 6–311++G (3df, 3pd) basis sets. Both the energy profile and natural bond orbital analysis predict that Sc– η 2 –C2 H2 and HCC–ScH complexes are promising hydrogen storage materials. The Sc– η 2 –(C2 H2 ) and HCC–ScH complexes can trap up to six hydrogen molecules, reaching gravimetric uptake capacities as high as 14.56 wt%. Thermo-chemistry calculations indicate two H2 in Sc– η 2 –C2 H2 (H2 )6 and four H2 in HCC–ScH(H2 )6 can be readily adsorbed at 77 K and desorbed at 298.15 K under atmospheric pressure, corresponding to the maximal reversible hydrogen storage abilities of 5.37 and 10.20 wt%, respectively. The further comparison between HCC–ScH(H2 ) and HCC–ScH − (2H) reveals that the charged state of Sc atom has a great influence on the hydrogen adsorption state and adsorption energy. Moreover, dimers may form in case of scandium-acetylene systems. The most stable (C2 H2 Sc)2 can adsorb ten H2 molecules, reaching the hydrogen storage capacity of 12.43 wt%. Thermo-chemistry calculations indicate the maximal reversible hydrogen storage capacities of Sc(C2 H2 )2 and (C2 H2 Sc)2 are 7.67 and 7.85 wt%, respectively. Graphical abstract: Highlights: Synthesized C2 H2 Sc can adsorb six H2 with a binding energy of 0.14–1.35 eV/H2 . Maximal retrievable hydrogen storage density at 77–298.15 K is 10.20 wt%. Operation mechanism of hydrogen storage on C2 H2 Sc was profoundly anatomized. Estimating the adsorption/desorption temperatures at 1 atm. Changing the charge of Sc can regulate the adsorption energy.